2015
DOI: 10.1097/01.ogx.0000462915.64193.1b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Findings Among Patients Referred for Clinical Whole-Exome Sequencing

Abstract: involves karyotyping, whereas in the Netherlands, patients who undergo amniocentesis have a more limited assessment only for trisomies 13, 18, and 21 and the sex chromosomes; thus, the tradeoff is a bit different.In addition, cfDNA is provided as a screening test for trisomies 13, 18, and 21, not just for Down syndrome. However, the performance characteristics of cfDNA for trisomies 13 and 18 are not as favorable as for T21, with a higher rate of falsenegative and false-positive results. In addition, a percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

25
520
3
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 373 publications
(557 citation statements)
references
References 12 publications
25
520
3
9
Order By: Relevance
“…1 While originally used almost exclusively for novel gene discovery, 2,3 WES is now routinely considered the approach of choice for the medical geneticists' most clinically challenging rare disease patients. [4][5][6][7][8][9] The diagnostic yield following clinical WES varies considerably; large cohorts have shown that the genetic basis of disease will be identified in 20%-60% of patients. [4][5][6][7][8][9][10] For those who receive a molecular diagnosis, not only does the diagnostic odyssey come to an end but also appropriate genetic counseling for family members becomes available, and in some cases disease management is tailored based on knowledge of the natural history of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 While originally used almost exclusively for novel gene discovery, 2,3 WES is now routinely considered the approach of choice for the medical geneticists' most clinically challenging rare disease patients. [4][5][6][7][8][9] The diagnostic yield following clinical WES varies considerably; large cohorts have shown that the genetic basis of disease will be identified in 20%-60% of patients. [4][5][6][7][8][9][10] For those who receive a molecular diagnosis, not only does the diagnostic odyssey come to an end but also appropriate genetic counseling for family members becomes available, and in some cases disease management is tailored based on knowledge of the natural history of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] The diagnostic yield following clinical WES varies considerably; large cohorts have shown that the genetic basis of disease will be identified in 20%-60% of patients. [4][5][6][7][8][9][10] For those who receive a molecular diagnosis, not only does the diagnostic odyssey come to an end but also appropriate genetic counseling for family members becomes available, and in some cases disease management is tailored based on knowledge of the natural history of the disease. 1,11 The process of arriving at a molecular diagnosis in the "solved" group of patients is not without its challenges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…fax: +617 264 8795; e-mail: kchristensen@ genetics.med.harvard.edu Received 23 March 2015, revised and accepted for publication 15 June 2015 Whole genome sequencing (WGS) may soon play an important role in primary and specialty care. Falling technical costs and turnaround time are making widespread WGS use feasible (1)(2)(3)(4), and it is already useful for diagnosing disease, informing treatment decisions, and assisting life decisions (1,(5)(6)(7)(8). Genomic sequencing is a key component of President Obama's Precision Medicine Initiative (9), and healthcare systems are developing the infrastructure to enhance the utility of genomics (10,11).…”
mentioning
confidence: 99%
“…Until recently, the reports of WES in Mendelian diseases were from research studies or case series (7,(9)(10)(11)(12)(13)(14). Three clinical laboratories performing WES on a clinical basis have reported a molecular diagnostic rate of 25-30% (3,5,15,16). Although these reports are important contributions on the molecular diagnostic rate of WES, they do not examine the clinical relevance of the molecular findings on the remaining 75%, or if the clinicians concurred with the laboratory's interpretation (3,5).…”
mentioning
confidence: 99%